A Maussian bargain: Accumulation by gift in the digital economy. Issue 1 (January 2020) - Fourcade, Marion; Kluttz, Daniel N
The harvesting of data about people, organizations, and things and their transformation into a form of capital is often described as a process of "accumulation by dispossession, " a pervasive loss of rights buttressed by predatory practices and legal violence. Yet this argument does not square well with the fact that enrollment into digital systems is often experienced (and presented by companies) as a much more benign process: signing up for a "free" service, responding to a "friend's" invitation, or being encouraged to "share" content. In this paper, we focus on the centrality of gifting and reciprocity to the business model and cultural imagination of digital capitalism. Relying on historical narratives and in-depth interviews with the designers and critics of digital systems, we explain the cultural genesis of these "give-to-get" relationships and analyze the socio-technical channels that structure them in practice. We suggest that the economic relation that develops as a result of a digital gift offering not only masks the structural asymmetry between giver and gifted but also permits the creation of the new commodity of personal data, obfuscates its true value, and naturalizes its private appropriation. We call this unique regime "accumulation by gift."